Proceedings of the Companion Publication of the 2015 Annual Conference on Genetic and Evolutionary Computation 2015
DOI: 10.1145/2739482.2764654
|View full text |Cite
|
Sign up to set email alerts
|

Explanation of Stagnation at Points that are not Local Optima in Particle Swarm Optimization by Potential Analysis

Abstract: Particle Swarm Optimization (PSO) is a nature-inspired meta-heuristic for solving continuous optimization problems. In [16,18], the potential of the particles of a swarm has been used to show that slightly modified PSO guarantees convergence to local optima. Here we show that under specific circumstances the unmodified PSO, even with swarm parameters known (from the literature) to be "good", almost surely does not yield convergence to a local optimum is provided. This undesirable phenomenon is called stagnatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The relative potential captures the importance of each dimension and in [4] it has been argued that if this relative potential is quite low for some dimensions then the PSO does not optimize them.…”
Section: E D Is the D Th Cartesian Unit Vector And ⊙ Is Element-wise mentioning
confidence: 99%
See 3 more Smart Citations
“…The relative potential captures the importance of each dimension and in [4] it has been argued that if this relative potential is quite low for some dimensions then the PSO does not optimize them.…”
Section: E D Is the D Th Cartesian Unit Vector And ⊙ Is Element-wise mentioning
confidence: 99%
“…Therefore it is obvious that the PSO actually optimizes only the last two dimensions. In [4] it has been argued that the relative potential in dimensions which are not optimized any longer decreases (on average) linearly in logarithmic scale. If only fixed precision is used, this insight would not be possible at all.…”
Section: (B) Evaluation With Self-adjusting Precisionmentioning
confidence: 99%
See 2 more Smart Citations
“…This early convergence effect is known as a "stagnation problem" and it occurs when particles stop changing their positions, generating an early convergence to a position not guaranteed to be the global or local minimum (Freitas et al 2020). Additionally, it has been theoretically and experimentally demonstrated that the PSO algorithm would not converge to the optimum solution if the number of used particles is very small for the problem (Raß et al 2015).…”
Section: The Particle Swarm Optimization Algorithmmentioning
confidence: 99%